Perancangan Performance Management System Divisi Purchase dengan Balance Score Card Framework dan Strategy MAP (Studi Kasus Rumah Sakit Bersalin X di Pacitan) - Resti P. Ari Widjaja (UNUSA Press, 2018)
Abstract: The business of health services is a business that is closely related to social responsibility because the object is human so that it cannot be equated with other businesses. Hospital as one of the health service facilities, has a role in increasing public awareness of the importance of health. A hospital is a unique and complex organization because it is a labor-intensive institution, has charac- teristics and functions and functions that are specific to the process of producing medical services and have various professional groups in the service of sufferers. This study aims to design a Perfor- mance Management System in order to analyze internal and external factors, facilitate the monitoring and evaluation process to improve the performance and competitive advantage of Rumah Sakit Bersalin X Pacitan as a whole and improve purchase division performance in particular. The re- search method used in this study is qualitative with purposive sampling for sampling techniques. The results of this study, that management of Rumah Sakit Bersalin X execute High Contacts Busi- ness Strategy by means of recruiting workers who have the competence, knowledge, skills and abilities as a core employee business company that cannot be excluded, because this workforce is an executor in the company and is very much needed to be maintained. It can be seen from learning and growth perspective, the companies prefer ‘people expertise’, by choosing workers who have expertise that is tailored to each division within the company. People expertise is prepared as the executor of the company’s strategies and plans that are seen in the internal process. The dominance of these people expertise that drives ‘operational excellence’ which is expected to increase cus- tomer equity and thus will affect the company’s overall income and profitability.